2015
DOI: 10.1016/j.stem.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Forces of Change: Mechanics Underlying Formation of Functional 3D Organ Buds

Abstract: 3D organ buds that can recapitulate organ function have myriad applications for regenerative and personalized medicine. Here, Takebe et al. (2015) describe a generalized method for organ bud formation, demonstrating that mechanosensitive mesenchymal stem cells drive condensation of heterotypic cell mixtures to create buds from diverse organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
4
9
0
Order By: Relevance
“…(c) Ninety days after transplantation we noted that the graft created connections with mouse vessels. (Wrighton & Kiessling, 2015). In accordance with our study, Candiello et al (2018) showed hESC-PP and ECs coculture in a 3D material (Amikagel, a kind of hydrogel) leads to organization of islet-like structures in vitro.…”
Section: Formation Of Po By Integrating Multiple Derivatives Of Humsupporting
confidence: 83%
“…(c) Ninety days after transplantation we noted that the graft created connections with mouse vessels. (Wrighton & Kiessling, 2015). In accordance with our study, Candiello et al (2018) showed hESC-PP and ECs coculture in a 3D material (Amikagel, a kind of hydrogel) leads to organization of islet-like structures in vitro.…”
Section: Formation Of Po By Integrating Multiple Derivatives Of Humsupporting
confidence: 83%
“…An exciting new area of research is related to the in vitro generation of organ-analogous structures called organoids 4 , 29 , 30 . This research has focused mainly on the molecular manipulation of homogenous cell populations and mechanical inputs are just starting to be considered in the field 29 , 30 . As our findings reveal that proper morphogenesis requires mechanical interaction between different tissues, we anticipate that the consideration of mechanical signals in the organoid field will increase the success of ex vivo engineered tissues.…”
mentioning
confidence: 99%
“…These dynamic, reciprocal cell–cell interactions have been harnessed to create a “kidney in a dish” by cellular self‐assembly, which has been shown to reproduce some organ functionality . To realize a clinically transplantable kidney, however, the inter‐related issues of vascularization, mass transfer of nutrients and adequate size and function of the organ must be addressed . Decellularized cadaveric kidney has been suggested as the ideal scaffold to provide structural and biochemical cues to promote cellular self‐assembly .…”
Section: Discussionmentioning
confidence: 99%
“…However, these organoids are typically much smaller than the native human organ and the implantation of large numbers of these small organoids to achieve sufficient function in human patients may not be clinically practical. It has been proposed that an alternative approach would be to utilize ECM scaffolds from decellularized cadaveric organs, which can drive cellular self‐assembly and recapitulate organ function …”
Section: Introductionmentioning
confidence: 99%